Dance Is an Accessible Physical Activity for People with Parkinson’s Disease - Sara Emmanouilidis; Madeleine E. Hackney; Susan C Slade; Hazel Heng; Dana Jazayeri; Meg E. Morris (Parkinson's Disease)
Objective. To evaluate the outcomes of face-to-face, digital, and virtual modes of dancing for people living with Parkinson’s disease (PD). Design. Systematic review informed by Cochrane and PRIMSA guidelines. Data Sources. Seven electronic databases were searched: AMED, Cochrane, PEDro, CINHAL, PsycINFO, EMBASE, and MEDLINE. Methods. Eligible studies were randomised controlled trials (RCT) and other trials with quantitative data. The PEDro scale evaluated risk of bias for RCTs. Joanna Briggs Institute instruments were used to critically appraise non-RCTs. The primary outcome was the feasibility of dance interventions, and the secondary outcomes included gait, balance, quality of life, and disability. Results. The search yielded 8,327 articles after duplicates were removed and 38 met the inclusion criteria. Seven were at high risk of bias, 20 had moderate risk of bias, and 11 had low risk of bias. There was moderately strong evidence that dance therapy was beneficial for balance, gait, quality of life, and disability. There was good adherence to digital delivery of dance interventions and, for people with PD, online dance was easy to access. Conclusion. Dancing is an accessible form of exercise that can benefit mobility and quality of life in people with PD. The COVID-19 pandemic and this review have drawn attention to the benefits of access to digital modes of physical activity for people living with chronic neurological conditions.